Penerapan Pendekatan Realıstıc Mathematıcs Educatıon (RME) Untuk Menıngkatkan Pemahaman Konsep Matematıs Sıswa Sekolah Dasar - Bernardus Richard Saputra; Ahmad Saefudin Fiqri; Hani Febrianti; Astri Mulianati (Journal of Innovation in Primary Education, 2022)
ABSTRACT The low understanding of students' mathematical concepts can be caused by the inaccurate way of delivering material by teachers who often convey mathematical material as finished products without building students' mathematical concepts. This study aims to improve students' understanding of mathematical concepts through a realistic mathematical approach using classroom action research methods. The researcher uses a double method in the form of a qualitative study as the main rule and quantitative as additional data. The research subjects were the sixth grade students of public elementary schools in the city of Bandung, totaling 40 students. The results of this study indicate that the percentage of students' understanding of mathematical concepts increases. The average value of student worksheets (LKPD) increased by 8.9 points in cycle 2 with an average value of 95 with very high criteria. In the aspect of understanding mathematical concepts, it increased by 14.58 points, with an average score of 92 with very high criteria. Understanding of mathematical concepts observed from filling out the evaluation sheet also increased with an average of 0.72 points with an average score of 3 .80 from the previous cycle one with an average of 3.08 with very good criteria. The percentage of students above the minimum requirement criteria is 77.5%, this proves an increase of 17.1%. Based on the results of this study, it can be concluded that the application of a realistic mathematical approach can improve the understanding of mathematical concepts in grade VI elementary school students. Keywords: Realistic Mathematics Approach, Mathematical Concepts Understanding ABSTRAK Pemahaman konsep matematis siswa yang rendah dapat disebabkan oleh kurang tepatnya cara penyampaian materi oleh guru yang seringkali menyampaikan materi matematika sebagai produk jadi tanpa membangun konsep matematis siswa. Penelitian ini bertujuan untuk meningkatkan pemahaman konsep matematis siswa melalui pendekatan matematika realistik menggunakan metode penelitian tindakan kelas. Peneliti menggunakan double method berbentuk kajian kualitatif sebagai kaidah utama dan kuantitatif sebagai data tambahan. Subjek penelitian adalah siswa kelas enam sekolah dasar negeri di kota Bandung, yang berjumlah 40 siswa. Hasil Penelitian ini menunjukkan bahwa persentase pemahaman konsep matematis siswa meningkat. Rata-rata nilai lembar kerja peserta didik (LKPD) meningkat 8,9 poin pada siklus 2 degan rata-rata nilai 95 dengan kriteria sangat tinggi. Pada aspek pemahaman konsep matematis megalami peningkatan sebesar 14,58 poin, dengan nilai rata-rata 92 dengan kriteria sangat tinggi.Pemahaman konsep matematis yang diamati dari pengisian lembar evaluasi juga menigkat dengan rata-rata sebesar 0,72 poin dengan skor rata-rata 3,80 dari sebelumnya pada siklus satu dengan rata-rata 3,08 dengan kriteria sangat baik. Persentase banyaknya siswa di atas kriteria ketentuan minimum sebesar 77,5% hal ini membuktikan peningkatan sebesar 17,1%. Berdasarkan berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa penerapan pendekatan matematika realistik dapat meningkatkan pemahaman konsep matematis siswa kelas VI sekolah dasar. Kata Kunci: Pendekatan Matematika Realistik, Pemahaman Konsep Matematis